A composite material lignin-based hydrothermal carbon and its preparation method and application
The hydrothermal treatment of lignin and combined with mechanical ball milling method to prepare composite lignin-based hydrothermal carbon, which solves many problems in fructose preparation in traditional catalytic methods, and achieves efficient and economical glucose isomerization into fructose.
Patent Information
- Application Number
- CN202411708026.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-27
AI Technical Summary
In the preparation of fructose, traditional biological enzyme catalytic methods have problems such as strict reaction conditions, high cost and easy enzyme inactivation. The synthesis process of solid catalysts is cumbersome, harsh conditions, low activity and poor selectivity.
The hydrothermal method is used to treat lignin to prepare lignin-based hydrothermal carbon, and metal acetate and borate are added through mechanical ball mills to form the composite lignin-based hydrothermal carbon, which is used as a catalyst to promote the isomerization of glucose into fructose.
The efficient catalytic glucose isomerization into fructose was achieved, with short reaction time and high selectivity, with a glucose conversion rate of 67.4%, and a fructose yield of 54.8%.
Smart Images

Figure CN119186548B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of chemical synthesis, and in particular relates to a composite material lignin-based hydrothermal carbon and a preparation method and application thereof. Background Art
[0002] As fossil energy is facing depletion and environmental pollution is aggravating, biomass is increasingly valued as a sustainable alternative resource. In particular, biomass is regarded as an ideal raw material for the production of high-value-added biochemicals such as 5-hydroxymethylfurfural and levulinic acid. In the conversion of biomass, the isomerization of glucose to fructose is a key step in the refining process. Traditional bioenzymatic catalysis methods have many challenges in the preparation of fructose, such as strict reaction conditions, high costs, and easy enzyme inactivation. In view of these problems, heterogeneous catalytic systems have attracted widespread attention from scientific research and industry as an emerging alternative. This catalytic system is expected to provide a more efficient, economical and stable solution for the preparation of fructose. However, the current solid catalysts have the problems of cumbersome synthesis process, harsh conditions, low activity and poor selectivity, and the catalyst needs to be further optimized to finally obtain fructose. For this purpose, a composite material lignin-based hydrothermal carbon and its preparation method and application are proposed. Summary of the invention
[0003] The object of the present invention is to provide a composite material lignin-based hydrothermal carbon and a preparation method and application thereof, aiming to solve the problems raised in the above background technology.
[0004] To achieve the above object, the present invention provides the following technical solutions:
[0005] A method for preparing a composite material lignin-based hydrothermal carbon comprises the following steps:
[0006] Step 1, treating lignin by hydrothermal method to obtain lignin-based hydrothermal carbon;
[0007] Step 2, mechanically ball milling the lignin-based hydrothermal carbon material obtained in step 1 and the metal acetate and borate;
[0008] Step 3: Wash the material obtained in step 2 with anhydrous ethanol and ultrapure water, and dry it to obtain a composite material lignin-based hydrothermal carbon material. The composite material lignin-based hydrothermal carbon material contains aluminum and boron, and the aluminum exists in the form of Al 3+ , boron exists in the form of B-OH and BO. The boron group is conducive to the adsorption of glucose and promotes the mass transfer of reaction substrates. The metal can promote the isomerization of glucose into fructose, thus achieving efficient catalytic reaction.
[0009] Furthermore, the step 1 is specifically as follows:
[0010] Disperse lignin in water, stir with a magnetic stirrer at room temperature, with a stirring speed of 500-1000 rpm (preferably 600-900 rpm, most preferably 700 rpm), and a stirring time of 0.1-1 h (preferably 0.1-0.5 h, most preferably 0.2 h); subject the mixed lignin solution to hydrothermal treatment, with a hydrothermal reaction temperature of 150-250 ° C (preferably 200 ° C), and a hydrothermal reaction time of 12-24 h (preferably 16-20 h, most preferably 18 h). After the hydrothermal treatment is completed, dry the hydrothermal product to obtain lignin-based hydrothermal carbon.
[0011] Furthermore, in step 1, the lignin is alkali lignin, sodium lignin sulfonate, lignin extracted from biomass, etc.
[0012] Furthermore, in step 2, the molar ratio of the lignin-based hydrothermal carbon material, the metal acetate and the borate is 1:(0.5-2):(0.5-2), preferably 1:1:1. The content of acetate added is preferably 0.1-4 mol, more preferably 0.1-3 mol.
[0013] Furthermore, in step 2, the metal acetate is aluminum acetate, iron acetate, magnesium acetate, tin acetate, etc.; the borate is boric acid or borax.
[0014] Furthermore, in step 2, the ball milling speed is 250-400 rpm (preferably 300-400 rpm, most preferably 350 rpm), and the reaction time is 2-8 h (preferably 3-6 h, most preferably 4 h).
[0015] Furthermore, in step 3, the amount of detergent anhydrous ethanol and ultrapure water is preferably 10-50 mL, more preferably 20-30 mL; the number of washing times is preferably 1-2 times; the separation method during the washing process is centrifugation, the rotation speed is preferably 10000 rpm, and the centrifugation time is preferably 3 min.
[0016] The specific washing process is: the product obtained after ball milling is mixed with anhydrous ethanol and ultrapure water, and then stirred and centrifuged in sequence. The stirring time is preferably 5-10 min; the stirring rate is preferably 200-300 rpm; and the stirring method is preferably magnetic stirring.
[0017] Furthermore, the drying temperature is preferably 55-80°C, more preferably 80°C; the drying time is preferably 10-24 hours, more preferably 12 hours. The present invention has no special requirements for drying equipment, and a common blast drying oven in the art can be used.
[0018] A composite material lignin-based hydrothermal carbon prepared according to the preparation method described above.
[0019] An application of the composite material lignin-based hydrothermal carbon described above in isomerization of glucose into fructose.
[0020] Furthermore, the application is specifically:
[0021] The composite material lignin-based hydrothermal carbon is used as a catalyst, and the catalyst, glucose and ethanol are evenly mixed to obtain a mixed solution, in which the mass concentration of glucose in the mixed solution is 5-100 g / L (preferably 10-90 g / L). The mixed solution is placed in a microwave reaction device for heating. After the reaction is completed, the upper liquid is taken out for dilution, and qualitative and quantitative analysis is performed using UPLC. The composite material lignin-based hydrothermal carbon catalyzes the isomerization of glucose into fructose and its derivatives 5-hydroxymethylfurfural and 5-ethoxymethylfurfural.
[0022] Furthermore, the mass ratio of glucose to catalyst is (1.5-10):1 (preferably 2:1); the heating temperature is 40-160°C (preferably 120-160°C), and the heating time is 0.1-8 h (preferably 0.3-2 h).
[0023] Furthermore, ethanol is preferably 95% ethanol (AR). In the present invention, ethanol is only used as a solvent and does not play a catalytic role. The present invention has no particular limitation on the source of ethanol, and products well known to those skilled in the art can be used.
[0024] Furthermore, the glucose isomerization reaction is preferably carried out under stirring conditions; the stirring rate is preferably 500-800 rpm; and the stirring method is preferably magnetic stirring.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] The present invention uses lignin as raw material to achieve the resource recycling of biomass; a highly active lignin-based hydrothermal carbon material is prepared by a hydrothermal method, and a highly active composite material lignin-based hydrothermal carbon material is prepared by combining a mechanical ball milling method, and the synthetic route is more convenient, green and safe; lignin can increase the surface functional groups through a hydrothermal process, and at the same time, the present invention introduces metals and boron ions into the catalyst through a mechanical ball milling process, so that the material can efficiently isomerize glucose into fructose, with a short reaction time and high selectivity. The composite material lignin-based hydrothermal carbon is prepared by the preparation method provided by the present invention, and a glucose conversion rate of 67.4% and a fructose yield of 54.8% can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a mapping diagram of the product obtained in Example 4; wherein (a) is the distribution of metals on the catalyst, and (b) is the distribution of boron ions on the catalyst.
[0028] Figure 2 These are XPS graphs of the products obtained in Examples 1-4; wherein (a) is the XPS graph of the product obtained in Example 1; (b) is the XPS graph of the product obtained in Example 2; (c) is the XPS graph of the product obtained in Example 3; and (d) is the XPS graph of the product obtained in Example 4.
[0029] Figure 3 The yield and conversion rate of fructose acid produced by catalytic oxidation of glucose at 140°C for 1 h for the products obtained in Examples 1-4. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0031] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0032] Example 1: A method for preparing lignin-based hydrothermal carbon, comprising the following steps:
[0033] 8 g of alkali lignin and 40 mL of water were placed in a 100 mL polytetrafluoroethylene hydrothermal autoclave and mixed by magnetic stirring. The magnetic stirring conditions were: speed 700 rpm, time 0.2 h; hydrothermal reaction conditions were: temperature 200 °C, time 18 h; and drying at 80 °C to obtain lignin-based hydrothermal carbon, namely LS-HC.
[0034] Figure 2 (a) is the XPS graph of the product, proving that there is no metal on the surface of the material.
[0035] Example 2: A method for preparing a composite material lignin-based hydrothermal carbon, the steps are as follows:
[0036] 1 g LS-HC was mixed with 0.62 g boric acid and then mechanically ball-milled (mass ratio of material to steel ball was 1:8). The ball-milling conditions were as follows: rotation speed of 350 rpm and time of 4 h. After being taken out, the mixture was washed with ultrapure water for 1-2 times, centrifuged and dried at 80 °C for 12 h to obtain a B-lignin-based hydrothermal carbon catalyst material, namely B-LS-HC.
[0037] The XPS results show that the boric acid content in the B-LS-HC prepared in this example is 1-15 mmol, more preferably 5-15 mmol.
[0038] Figure 2 (b) is the XPS graph of the product, proving the presence of B ions on the surface of the material.
[0039] Example 3: A method for preparing a composite material lignin-based hydrothermal carbon, the steps are as follows:
[0040] 1 g LS-HC was mixed with 2.04 g aluminum acetate and then mechanically ball-milled (mass ratio of material to steel ball was 1:8). The ball-milling conditions were as follows: rotation speed of 350 rpm and time of 4 h. The mixture was taken out and washed with ultrapure water for 1-2 times. The material was centrifuged and dried at 80 °C for 12 h to obtain the Al-added lignin-based hydrothermal carbon catalyst material, namely Al-LS-HC.
[0041] It is calculated by XPS results that the content of aluminum acetate added in the Al-LS-HC prepared in this example is 1-15 mmol, more preferably 5-15 mmol.
[0042] Figure 2 (c) is the XPS image of the product, proving the presence of metallic aluminum on the surface of the material.
[0043] Example 4: A method for preparing a composite material lignin-based hydrothermal carbon, comprising the following steps:
[0044] 1 g LS-HC was mixed with 2.04 g aluminum acetate and 0.62 g boric acid and then mechanically ball-milled (mass ratio of material to steel ball was 1:8). The ball-milling conditions were as follows: rotation speed of 350 rpm and time of 4 h. The mixture was taken out and washed with ultrapure water for 1-2 times. The material was centrifuged and dried at 80 °C for 12 h to obtain a lignin-based hydrothermal carbon catalyst material with added B and Al, namely Al-B-LS-HC.
[0045] It was calculated by XPS results that the content of aluminum acetate added in the Al-B-LS-HC prepared in this example was 1-15 mmol, more preferably 5-15 mmol; the content of boric acid added was 1-15 mmol, more preferably 5-15 mmol.
[0046] Figure 1 This is the mapping diagram of the product, which proves that metallic aluminum and boron ions are evenly distributed on the catalyst.
[0047] Figure 2 (d) is the XPS image of the product, proving the presence of metallic aluminum and boron ions on the surface of the material.
[0048] Table 1 shows the change of the yield of glucose isomerization to fructose catalyzed by the material prepared in Example 4 at different reaction temperatures as a function of reaction time.
[0049] Table 1 Effect of reaction temperature on glucose isomerization over Al-B-LS-HC catalyst
[0050] (Reaction conditions: glucose 0.18 g, catalyst 0.09 g, ethanol 5 mL)
[0051]
[0052] As the reaction temperature increases and the reaction time prolongs, it can be found from Table 1 that the fructose yield reaches a maximum value of 54.8% when the reaction is performed at 140 °C for 1 h.
[0053] Application Example 1: A method for synthesizing fructose, the steps are as follows:
[0054] 0.09 g of LS-HC prepared in Example 1 was mixed with 0.18 g of glucose and 5 mL of ethanol to obtain a mixed solution (the mass concentration of glucose in the mixed solution was 36 g / L, and the mass ratio of the catalyst to glucose was 1:2). The mixed solution was then transferred to a 10 mL microwave reaction bottle and placed in a microwave reactor for glucose isomerization reaction, accompanied by magnetic stirring at a rate of 600 rpm. The reaction was completed after 1 h, and then the solution was filtered using a filter membrane, and the product was determined by liquid chromatography to calculate the yield of fructose.
[0055] The conditions of liquid chromatography are as follows: the chromatographic column is Shodex SH1011, the mobile phase is 0.5 mL / min sulfuric acid solution (5 mM), the column temperature is 50 °C, the injection volume is 10 uL. The glucose and fructose detectors are differential detectors, and the detector temperature is 35 °C.
[0056] The final measured glucose conversion rate was 31.2% and the fructose yield was 18% (see Figure 3 ).
[0057] Application Example 2: A method for synthesizing fructose, the steps are as follows:
[0058] 0.09 g of B-LS-HC prepared in Example 2 was mixed with 0.18 g of glucose and 5 mL of ethanol to obtain a mixed solution (the mass concentration of glucose in the mixed solution was 36 g / L, and the mass ratio of the catalyst to glucose was 1:2). The mixed solution was then transferred to a 10 mL microwave reaction bottle and placed in a microwave reactor for glucose isomerization reaction, accompanied by magnetic stirring at a rate of 600 rpm. The reaction was completed after 1 h, and then the solution was filtered with a filter membrane, and the product was determined by liquid chromatography to calculate the yield of fructose.
[0059] The conditions of the liquid chromatography are the same as those of the liquid chromatography in Application Example 1.
[0060] The final measured glucose conversion rate was 26.4% and the fructose yield was 16.8% (see Figure 3 ).
[0061] Application Example 3: A method for synthesizing fructose, the steps are as follows:
[0062] 0.09 g of Al-LS-HC prepared in Example 3 was mixed with 0.18 g of glucose and 5 mL of ethanol to obtain a mixed solution (the mass concentration of glucose in the mixed solution was 36 g / L, and the mass ratio of the catalyst to glucose was 1:2). The mixed solution was then transferred to a 10 mL microwave reaction bottle and placed in a microwave reactor for glucose isomerization reaction accompanied by magnetic stirring at a rate of 600 rpm. The reaction was completed after 1 h, and then the solution was filtered with a filter membrane, and the product was determined by liquid chromatography to calculate the yield of fructose.
[0063] The conditions of the liquid chromatography are the same as those of the liquid chromatography in Application Example 1.
[0064] The final measured glucose conversion rate was 71.8% and the fructose yield was 24.2% (see Figure 3 ).
[0065] Application Example 4: A method for synthesizing fructose, the steps are as follows:
[0066] 0.09 g of Al-B-LS-HC prepared in Example 4 was mixed with 0.18 g of glucose and 5 mL of ethanol to obtain a mixed solution (the mass concentration of glucose in the mixed solution was 36 g / L, and the mass ratio of the catalyst to glucose was 1:2). The mixed solution was then transferred to a 10 mL microwave reaction bottle and placed in a microwave reactor for glucose isomerization reaction, accompanied by magnetic stirring at a rate of 600 rpm. The reaction was completed after 1 h, and then the solution was filtered with a filter membrane, and the product was determined by liquid chromatography to calculate the yield of fructose.
[0067] The conditions of the liquid chromatography are the same as those of the liquid chromatography in Application Example 1.
[0068] The final measured glucose conversion rate was 67.4% and the fructose yield was 54.8% (see Figure 3 ).
[0069] In summary, by using the preparation method provided by the present invention to prepare the composite material lignin-based hydrothermal carbon, a glucose conversion rate of 67.4% and a fructose yield of 54.8% can be achieved.
[0070] The calculation formulas for the conversion rate and yield in the above application examples are:
[0071] Glucose conversion rate (%) = glucose concentration after reaction / initial glucose concentration × 100%;
[0072] Fructose yield (%) = fructose production (mol) / glucose unit (mol) × 100%.
[0073] The above are only preferred implementation modes of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. A method for preparing a composite material lignin-based hydrothermal carbon, characterized in that: The following steps are involved: Step 1, treating lignin by hydrothermal method to obtain lignin-based hydrothermal carbon; Step 2, mechanically ball milling the lignin-based hydrothermal carbon material obtained in step 1 and the metal acetate and borate; Step 3, washing the material obtained in step 2 with anhydrous ethanol and ultrapure water, and drying to obtain a composite material lignin-based hydrothermal carbon material; The step 1 is specifically as follows: dispersing lignin in water, stirring with a magnetic stirrer at room temperature, with a stirring speed of 500-1000 rpm and a stirring time of 0.1-1 h; subjecting the mixed lignin solution to hydrothermal treatment, with a hydrothermal reaction temperature of 150-250 ° C and a hydrothermal reaction time of 12-24 h. After the hydrothermal treatment is completed, drying the hydrothermal product to obtain lignin-based hydrothermal carbon; In the step 1, the lignin is alkali lignin, sodium lignin sulfonate or lignin extracted from biomass; In the step 2, the molar ratio of the lignin-based hydrothermal carbon material, the metal acetate and the borate is 1:(0.5-2):(0.5-2); In step 2, the metal acetate is aluminum acetate; the borate is boric acid or borax; In the step 2, the ball milling speed is 250-400 rpm, and the reaction time is 2-8 h.
2. A composite material lignin-based hydrothermal carbon prepared according to the preparation method according to claim 1.
3. Use of the composite material lignin-based hydrothermal carbon according to claim 2 in the isomerization of glucose into fructose.
4. The use according to claim 3, characterized in that: The application is specifically: The composite material lignin-based hydrothermal carbon is used as a catalyst, and the catalyst, glucose and ethanol are evenly mixed to obtain a mixed solution. The mass concentration of glucose in the mixed solution is 5-100 g / L. The mixed solution is placed in a microwave reaction device for heating. After the reaction is completed, the upper liquid is taken out for dilution, and qualitative and quantitative analysis is performed using UPLC. The composite material lignin-based hydrothermal carbon catalyzes the isomerization of glucose into fructose and its derivatives 5-hydroxymethylfurfural and 5-ethoxymethylfurfural.
5. The use according to claim 4, characterized in that: The mass ratio of glucose to catalyst is 1:(1.5-10); the heating temperature is 40-160° C., and the heating time is 0.1-8 h.
Citation Information
Patent Citations
Metal modified lignin-based functional carbon as well as preparation method and application thereof
CN117861728A